Association of serotype with respiratory presentations of pneumococcal infection, Ontario, Canada, 2003–2011. Issue 6 (3rd February 2016) - Shigayeva, Altynay; Rudnick, Wallis; Green, Karen; Tyrrell, Gregory; Demczuk, Walter H.B.; Gold, Wayne L.; Gubbay, Jonathan; Jamieson, Frances; Plevneshi, Agron; Pong-Porter, Sylvia; Richardson, Susan; McGeer, Allison; et al.
Abstract: Background: Pneumococcal disease burden is difficult to quantify due to limited data regarding non-bacteremic disease. We assessed serotype-specific differences in pneumococcal disease presentations in adults in Toronto, Canada. Methods: From 2003 to 2011, population-based surveillance for invasive pneumococcal disease was conducted and respiratory pneumococcal isolates collected in Metropolitan Toronto/Peel Region, Canada. Episodes of care were classified into disease categories. Results: Of 3105 eligible cases of IPD, 2060 cases were bacteremic pneumonia, and 1045 bacteremia without pneumonia. Of 2751 eligible respiratory cases, 1542 (56.0%) were non-bacteremic pneumonia (NBPP), 467 (17.0%) were other acute respiratory infection (oARI), and 742 (27.0%) were isolates representing colonization. Serotypes 3 (11.3%), 19A (8.4%) and 22F (6.2%) were the most common; serotypes 1, 5, and 8 were rare. Serotypes 4, 14, 7F, 9V, 12F, 14, 19A and 6C were over-represented in bacteremic disease, and serotypes 3, 6A, 11A, 19F, 23A, 23F, 35B, 35F were more common in NBPP. The proportion of cases due to PCV7 serotypes declined from 48.7% to 8.7% in bacteremic pneumonia, from 35.3% to 10.9% in NBPP, from 34.2% to 7.5% in oARI, and from 38.7% to 12.2% in colonizing isolates. In 2010–2011, PCV13 serotypes accounted for 62.6% of isolates associated with bacteremic pneumonia, 42.0% of bacteremia without pneumonia, 41.1% of NBPP, 25.7% of oARI, and 32.9% of colonizing isolates. Conclusions: Serotype distributions differ significantly in different presentations of pneumococcal disease. Herd protection due to PCV7 has changed serotype distribution, but PCV13 serotypes remain important in all categories of disease.